2016
DOI: 10.1111/bcpt.12621
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Pharmacokinetics and Pharmacodynamics of the Selective Glucocorticoid Receptor Modulator AZD5423 after Inhalation in Healthy Volunteers

Abstract: AZD5423 is a selective glucocorticosteroid receptor modulator developed for the inhaled use in asthma and COPD. This study reports the initial, first-in-man, single and repeat dose-escalating studies in healthy male individuals, including one cohort of male Japanese individuals. Inhaled, nebulized AZD5423 was safe and well tolerated up to and including the highest doses tested for up to 2 weeks of once-daily treatment. Plasma exposure suggested dose-proportional pharmacokinetics and dose-related effects on 24-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 9 publications
(19 reference statements)
2
14
0
Order By: Relevance
“…However, in a PK trial in healthy individuals, the Turbuhaler powder formulation of AZD5423 performed as expected . Also in the present study, the plasma concentration data of AZD5423 versus time were similar to the dose‐normalized plasma concentrations of AZD5423 found in healthy individuals when the PK of AZD5423 was studied over a wide dose range . In addition, plasma cortisol suppression was what would have been expected from the previous tolerability trial: In the multiple ascending dose study in healthy individuals, plasma cortisol was significantly suppressed by AZD5423 versus placebo (29% suppression) at 375 μg lung‐deposited dose via nebulizer, while no suppression could be distinguished at doses below 300 μg .…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…However, in a PK trial in healthy individuals, the Turbuhaler powder formulation of AZD5423 performed as expected . Also in the present study, the plasma concentration data of AZD5423 versus time were similar to the dose‐normalized plasma concentrations of AZD5423 found in healthy individuals when the PK of AZD5423 was studied over a wide dose range . In addition, plasma cortisol suppression was what would have been expected from the previous tolerability trial: In the multiple ascending dose study in healthy individuals, plasma cortisol was significantly suppressed by AZD5423 versus placebo (29% suppression) at 375 μg lung‐deposited dose via nebulizer, while no suppression could be distinguished at doses below 300 μg .…”
Section: Discussionsupporting
confidence: 85%
“…Also in the present study, the plasma concentration data of AZD5423 versus time were similar to the dose‐normalized plasma concentrations of AZD5423 found in healthy individuals when the PK of AZD5423 was studied over a wide dose range . In addition, plasma cortisol suppression was what would have been expected from the previous tolerability trial: In the multiple ascending dose study in healthy individuals, plasma cortisol was significantly suppressed by AZD5423 versus placebo (29% suppression) at 375 μg lung‐deposited dose via nebulizer, while no suppression could be distinguished at doses below 300 μg . In the present study, a suppression of 16% was observed at 12 weeks following 404 μg predicted lung‐deposited dose of AZD5423 via Turbuhaler (corresponding to 800 μg daily delivered dose).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Since the late 1990s, this has triggered researchers to synthetize various SEGRA and SEGRM compounds, with GSK866 and mapracorat being the prototypes of this non-steroidal class of compounds, in which bulky, bicyclic aromatic substituents account for the structural similarity to corticoids ( 7 , 13 15 , 18 20 ). In vivo efficacy for SEGRA/SEGRM compounds with reduced side effects has already been demonstrated for treatment of acute infections, such as rheumatoid arthritis, asthma, and colitis, in the clinic ( 20 22 ).…”
Section: Introductionmentioning
confidence: 99%